EFFECT OF AUDIT FIRM SIZE AND AUDITORS’ TENURE ON FINANCIAL STATEMENT FRAUD OF LISTED NON-FINANCIAL FIRMS ON THE NIGERIAN EXCHANGE GROUP (Journal of Global Accounting, 2024)
This paper aimed at ascertaining the effect of audit firm size and auditors’ tenure on financial statement fraud of listed non-financial firms on the Nigerian Exchange Group for a period of 2011 to 2022. The study employs ex-post facto design and secondary data. The population consisted of ninety-five (95) non-financial firms listed in the Nigerian Exchange Group as at December, 2022. The final sample consisted of seven-six (76) non-financial firms selected using purposive sampling. We applied Robust least square regression analysis in addition to the application of Beniesh M-score model to proxy the likelihood of financial statement fraud where applicable, via the E-view 9 software for the panel data in order to determine the relationship between the variables. Findings from this study indicated that audit firm size and auditors’ tenure have no significant positive effect on financial statement fraud of non-financial firms listed on the Nigerian Exchange Group. On the basis of the above findings, we recommended that since audit firm size has no significant positive effect on financial statement fraud of listed non-financial firms, then is not necessary because whether firm engage one of the big 4 audit firms or one of non-big 4 audit firms does not necessarily eliminate financial statement fraud. The study also recommends that regulatory authority should ensure a moderate audit tenure of 5years, to enable the audit firm time to understand client’s business and give a thorough audit to reduce financial statement fraud.
Keywords: Audit Firm Size; Auditors’ Tenure; Fraud; Financial Statement Fraud